Effective Leadership of Kindergarten Principals in Facing the Impact of Learning Loss in Kindergartner During the Covid-19 Pandemic - Ocih Setiasih; Aisah Karunia Rahayu; Roby Naufal Arzaqi (SEAMEO CECCEP, 2023)
Online and home learning during the COVID-19 pandemic present several challenges and risks of learning loss that have a long-term impact on children. Because of this, kindergarten principals are encouraged to take practical and strategic steps in dealing with crises for the sake of the continuity and sustainability of education. Thus, this study aims at determining the effective leadership of kindergarten principals in dealing with the impact of learning loss in early childhood during the COVID-19 pandemic. The approach used is qualitative with a case study design and four research participants, namely three principals with different geographical backgrounds. Data were collected through interviews and analyzed using thematic analysis. The research findings show that all participants have had proactive leadership in the ability to choose responses to the pandemic to improve teaching quality, institutional resilience, and the development of further innovation. They took initiative and anticipatory steps to reduce the impact of learning loss, such as blended learning, visiting teacher programs, literacy movements, and parenting programs. Kindergarten principals with rural geographical conditions have not shown a win-win mindset, especially in the aspect of negotiating and finding alternative solutions together, as evidenced by the lack of school efforts to build agreements with school members in overcoming learning loss in children during online learning. Furthermore, kindergartens with suburban geographical conditions did not reflect self-honing behavior in terms of physical dimensions because the pandemic has added a burden to the mind and reduced rest time, which hinders the kindergarten principal in ensuring his physical health.